Changes in cellular components of peritoneal fluid of white mice with infection caused by Yersinia pestis with different plasmid profile - T. P. Starovoytova; T. A. Ivanova; G. B. Mukhturgin; S. A. Vityazeva; V. I. Dubrovina; K. M. Korytov; S. V. Balakhonov (Acta Biomedica Scientifica)
The article presents the data on the influence of Yersinia pestis plasmid profile on subpopulation structure of mononuclear cells of peritoneal fluid of mice at the early stages of infectious process. It was showed that change of cellular composition of peritoneal fluid of the experimental animals depended on the plasmid profile of Yersinia pestis strains. The phase character in the changes of quantitative composition of the mast cells of peritoneal fluid of white mice infected with Y. pestis strains with different plasmid spectrum was determined.